FAKTOR-FAKTOR YANG MEMPENGARUHI KAWASAN AGROPOLITAN DI KABUPATEN KUTAI KARTANEGARA - ERNA KURNIATI (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this study is to know the factors of the agropolitan improvement in Kutai Kartanegara and to know the dominant factors in the Agropolitan improvement in Kutai Kartanegara The instrument of this study is data regression panel by testing Fixed Effect, Random Effect and Housman. Based on the measurement of the study, the researcher found Y= 0.836 + 0.749 log(LP) - 0,198 log(TK) - 0.003 log(CH). Result the coefficient of correlation numerical about R= 0.971 that is mean 97.1 %. This measurement showed the close relationship between variable of area, labor and rainfall. Based on the result of the study, the variable give sufficient effect to the alteration of Agropolitan variable. Meanwhile, Adjusted R2 is 0.969. It is means that the alteration of variable area, labor and rainfall can explain the variable alteration about 96.95.Keywords: Agropolitan, Area, Labor, Rainfall, Fixed Effect